'The snake biting its own tail': Karl Barth on the modern promise of politics. Issue 2 (15th March 2021) - Keedus, Liisi
ABSTRACT: Barth scholarship, largely theological in focus, has highlighted his lifelong political engagement, emphasising his early socialist activism, his resolute opposition to the Great War and nationalism, and his authorship of the Barmen declaration. This paper focuses on a series of lectures by Barth, published as Protestant Theology in the 19th Century. Its Pre-history and History (1927–1933/1947), and argues that these lectures reveal his more comprehensive interest and approach to the problem of political modernity than has commonly been allowed for. As such, they illuminate and connect some of the main political concerns and themes in Barth's thought, especially during the interwar period, usually considered in isolation from each other, such as social justice, revolution, nationalism, totalitarianism, internationalism, resistance, liberalism and Christian politics.